ANALISIS RENCANA BISNIS UNTUK MENINGKATKAN DAYA SAING YANG BERKELANJUTAN PADA USAHA DJAYIT KONVEKSI DI BANDAR LAMPUNG - Hepiana Patmarina; Dimas Adji Prakasa; Ardansyah Ardansyah (Universitas Mitra Indonesia, 2021)
ABSTRACT The purpose of this study is to determine the business rencanaes that can be done to increase the competitiveness of the Convection Djayit Business in Bandar Lampung. The population of this research is Djayit Konveksi with competitors, namely Adeeva Konveksi, and Sunyin Konveksi. The sample in the study was the whole population, namely 3 respondents.Sources of data are interview techniques and questionnaires to Djayit Konveksi in Bandar Lampung and competitors. The data collection method is primary data which is done by means of observation, documentation study and questionnaire. The method of analysis uses a SWOT analysis. The results of the cartesius diagram research, where Djayit Convection is in quadrant I, then the business strategy that can be implemented is the generic strategy. The rencanaes that can be carried out are: Low Cost Rencanaes (cost leadership), Differentiation Rencanaes, and Focus Rencanaes (focus)Keywords: Competitiveness and Business Strategy.